Effect of vaccination on SARS-CoV-2 reinfection risk: a case–control study in the Republic of Cyprus. (March 2022) - Quattrocchi, Annalisa; Tsioutis, Constantinos; Demetriou, Anna; Kyprianou, Theopisti; Athanasiadou, Maria; Silvestros, Valentinos; Mamais, Ioannis; Demetriou, Christiana A; Theophanous, Fani; Soteriou, Soteroulla; Gregoriadou, Chryso; Anastasiou, Eleni; et al.
Abstract: Objectives: We explored the effectiveness of COVID-19 vaccines in preventing reinfection in the Republic of Cyprus. Study design: This was a matched case–control study (1:2). Methods: Cases were adults with a first episode of SARS-CoV-2 infection in 2020 and a second episode (i.e. reinfection) between June and August 2021. Controls were adults with only one infection episode in 2020 (i.e. not reinfected). Matching was performed by age, gender, and week of diagnosis for the first episode. The reinfection date of a case was applied to the matched controls for estimating full or partial vaccination status. Cases and controls were classified as unvaccinated, partially vaccinated (i.e. vaccination series not completed or final dose received ≤14 days before the reinfection date), or fully vaccinated (i.e. final dose received >14 days before the reinfection date). Conditional logistic regression was performed to calculate odds ratios and 95% confidence intervals for full or partial vaccination, against no vaccination, between controls and cases. Results: This study showed that controls were more likely to be vaccinated (odds ratio for full vaccination: 5.51, 95% confidence interval: 2.43–12.49) than cases. Conclusions: This finding answers a pressing question of the public and supports the offer of vaccination to people with previous SARS-CoV-2 infection.